2019
DOI: 10.1055/s-0038-1676588
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Patients' Perceptions of the Patient Portal Experience with OpenNotes

Abstract: Background Access to medical encounter notes (OpenNotes) is believed to empower patients and improve the quality and safety of care. The impact of such access is not well understood beyond select health care systems and notes from primary care providers. Objectives This article analyzes patients' perceptions about the patient portal experience with access to primary care and specialist's notes and evaluates free-text comments as an improvement opportunity. Materials and Methods Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 17 publications
8
71
0
Order By: Relevance
“…Patients can be informed about their health conditions in a variety of ways, including receiving calls and messages from doctors, seeing doctors during appointments, or by accessing a patient web portal. Studies have found that many patients who used the health portal at some point in the previous year had a more positive feeling about their health care experiences [37,50]. By accessing personal health records (PHRs), patients can see their health records and will be able to gain a better understanding of their health [37].…”
Section: Benefits Of a Patient Portal For Patient Engagementmentioning
confidence: 99%
“…Patients can be informed about their health conditions in a variety of ways, including receiving calls and messages from doctors, seeing doctors during appointments, or by accessing a patient web portal. Studies have found that many patients who used the health portal at some point in the previous year had a more positive feeling about their health care experiences [37,50]. By accessing personal health records (PHRs), patients can see their health records and will be able to gain a better understanding of their health [37].…”
Section: Benefits Of a Patient Portal For Patient Engagementmentioning
confidence: 99%
“…9,10 Physicians also experienced benefits, most commonly citing strengthened relationships with their patients, and most reported no difficulties in their practice. 10 Since that time, a growing body of evidence supports sharing notes with patients to improve patient engagement, 11,12,13,14,15 enhance patient safety, 16,17,18 and foster trusting relationships and shared decision making. 19,20,21,22 Ethics Consultation Services Should Share Consultation Notes Although clinicians increasingly share EHR notes through the portal, 23 there has been little discussion of whether ethics consultation services should do the same.…”
Section: Current Documentation and Sharing Practicesmentioning
confidence: 99%
“…2 Other initiatives have pushed for increased transparency of all personal medical information, such as Open-Notes, and have been met with positive responses from patients. 3 At the same time, patients are increasingly capable of generating their own health data through mobile health technologies and patient-reported outcomes (PROs) surveys. 4,5 Patients can immediately visualize their PROs and other patient-generated health data (PGHD) easily and quickly through the same electronic systems, including smartphone applications and wearables.…”
Section: Background and Significancementioning
confidence: 99%